One way and another - Phillips, Adam (London : Hamish Hamilton, 2013)
Throughout his career, Adam Phillips has lent a fresh and incisive dimension to the art of the literary essay. This title collects nineteen pieces that have best defined his thinking - including 'On Tickling', 'On Being Bored' and 'Clutter: A Case History' - along with a selection of new writings and an introduction by a Man Booker Prize winner.--
Machine generated contents note: On Tickling -- On Being Bored -- Worrying and Its Discontents -- Looking at Obstacles -- First Hates -- On Success -- Contingency for Beginners -- The Uses of Forgetting -- Clutter -- Narcissism, For and Against -- Bombs Away -- Against Inhibition -- Superiorities -- Making It Old -- The Master-Mind Lectures -- For the Family -- The Dream Horizon -- The Uses of Desire -- Talking Nonsense and Knowing When to Stop -- Arbus's Freaks -- My Happiness Right or Wrong -- Judas for Now -- Punishing Parents -- On Compromise -- Psychoanalysis; or, Is It Worth It? -- Coda: Up to a Point.
Keywords: Psychoanalysis; Psychoanalytic Therapy